Influence of Western Pacific Madden–Julian Oscillation on New York City's Record‐Breaking Air Pollution in Early June 2023 - Yan Zhu; Pang‐chi Hsu; Yitian Qian (Geophysical Research Letters)
Abstract In early June 2023, New York City (NYC) and other cities in the northeastern US experienced a severe air pollution event. Although reports associated this hazardous pollution event with the smoke from Canadian wildfires, the factors triggering the southward waft of the smoke remain unclear. We found the northerly anomaly that transported the smoke was linked to the Rossby wave train excited by the Madden–Julian Oscillation (MJO) over the Philippine Sea, which led to the formation of an enhanced northerly at the western edge of the cyclonic anomaly over the East Coast–North Atlantic. When the MJO convection left the western Pacific, the disorganized teleconnection caused the pollution to dissipate. Observational findings were further supported by model simulations and predictions. These results suggest that monitoring and predictions of MJO activity may help mitigate air pollution events over the northeastern US during Canadian wildfire seasons.